PENGARUH KREATIVITAS TERHADAP SELF EFFICACY MAHASISWA JURUSAN PENDIDIKAN EKONOMI FAKULTAS EKONOMI UNESA - PRIYANTINI, MERLYAWATI (Jurnal Pendidikan Tata Niaga (JPTN), 2013)
Intense competition in the business work need the high quality of human resources. the Department of Economics Faculty of Economics UNESA give entrepreneurship courses to provide skills to the students. the students are the next generation who be came professionals human and have highly creativity. They can bring self efficacy so the can compete in business world. The purpose of this research is to know existence of the influence of creativity on self-efficacy of students department in Economics Faculty Education ekomoni UNESA.This research is descriptive research which use a quantitative approach, it procedure that produces descriptive data in the form of words of explanation of the results of quantitative data in the form of numbers from the study questionnaire. Research population is all students majoring in Economics education class of 2009, amounting ti 252 student whilw the sample totaled 155 students sampling technique using proporsional sampling. Data analysis used in this study is a simlpe regression analysis, The results of this research show that creativity self-efficacy significantly influence the of 26.5%. Keywords: creativity and self-efficacy